(NrIMSKIJ (B-(NkORSAKOW(B. (NrOMANSY(B. (NpOLNOE SOBRANIE SO^INENIJ(B. 1844-1908s (NrOMANSY(B. (NTOM SOROK PQTYJ(B.s - (NnIKOLAJ aNDREKWI^s ((NmOSKWAs (NmUZYKAs, 1946)
(NpERWOE ZNAKOMSTWO nIKOLAQ aNDREEWI^A rIMSKOGO(B- (NkORSKAKOWA S ROMANSNOJ LITERATUROJ KAK S OSOBYM VANROMs
Keywords: (NrOMANSs